Comparison of Patients' Phenotypes, Guideline-Directed Recommendations Compliance and Rates of Cardiotoxicity between Caribbean and United States Cardio-oncology Programs. Issue 1 (20th September 2022) - Piña, Pamela; Taveras, Amparo; Khan, Amir; Coyle, Justin; Bueno, Victor; Shah, Nishit; Cuello, Luis; Collado, Santiago; Mauer, Ann; Danciu, Sorin; Herrera, Cesar J.
Background: Little is known about the characteristics of oncological patients, cancer therapy-induced cardiotoxicity, and guidelines-directed interventions in the Caribbean; analysis of cardio-oncology services may shed light on this and clarify links between ethnicity, cultural, and local socioeconomic factors. Objectives: This study compared patients' phenotypes, adherence to guidelines recommendations, and patterns of cardiotoxicity between two cardio-oncology programs: one in the Dominican Republic (DR) and the other in Chicago IL, United States (US). Methods: Patients being considered for or treated with potentially cardiotoxic drugs were followed before, during, and after chemotherapy through both cardio-oncology clinics, where we recorded and compared clinical, demographic, and echocardiographic data. Results: We studied 597 consecutive patients, 330 (55%) from the DR and 267 (45%) from the US. DR vs. US mean age 55± 13/52 ± 13 years; female 77/87% (p < 0.001); breast cancer 57/73% (p < 0.001); treated with anthracyclines + taxanes 47/40% (p = 0.151); monoclonal antibodies + taxanes or platins 37/45% (p < 0.001). Cardiotoxicity DR vs. US occurred in 15/7% (p = 0.001); multivariate logistic regression (OR 2.29; 95% CI, 1.31–3.99; p < 0.005) did not identify age >60, HTN, DM, BMI, tobacco or chemotherapy as predictors. Compliance with ASCO guidelines was similar among both cohorts. Conclusion: Compared to the US cohort, the Caribbean cohort of cancer patients has similar rates of CV risk factors but a higher likelihood of developing drug-induced LV dysfunction. Programs' compliance with ASCO guidelines was equivalent. While further research is needed to ascertain regional variations of cardiotoxicity, these findings underline the relevance of cardio-oncology services in nations with limited resources and high CV risk.